2019
DOI: 10.3390/pr8010022
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Structural Control Analysis of an Offshore Wind Turbine Tower System

Abstract: This paper investigates the vibration control, stability, and energy transfer of the offshore wind turbine tower system with control force and nonlinearity terms. A nonlinear proportional derivative (NPD) controller was connected to the system to reduce a high oscillation amplitude and to transfer the energy in the wind turbine system. Furthermore, the averaging method and Poincaré maps were used with respect to the controlled system to study the stability and bifurcation analysis in the worst resonance cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Considering that the construction and operation costs of offshore wind turbines are higher than those of onshore wind turbines, it has become a trend to develop ultra-large power offshore wind turbines. Offshore wind turbine tower is subject to the combined action of wind load and wave load at the same time, and the stress situation is more complicated than that of onshore wind turbine, so it is necessary to calculate the environmental load in detail [1][2] and carry out the design technology research of the tower to improve its working performance [3][4][5]. In addition, the operation and maintenance cost of offshore wind turbine is higher than that of onshore wind turbine.…”
Section: Prefacementioning
confidence: 99%
“…Considering that the construction and operation costs of offshore wind turbines are higher than those of onshore wind turbines, it has become a trend to develop ultra-large power offshore wind turbines. Offshore wind turbine tower is subject to the combined action of wind load and wave load at the same time, and the stress situation is more complicated than that of onshore wind turbine, so it is necessary to calculate the environmental load in detail [1][2] and carry out the design technology research of the tower to improve its working performance [3][4][5]. In addition, the operation and maintenance cost of offshore wind turbine is higher than that of onshore wind turbine.…”
Section: Prefacementioning
confidence: 99%
“…Hamed et al demonstrated that by applying nonlinear structural control to an offshore wind turbine system. They focused on vibration control, stability, and energy transfer by using advanced control techniques, yielding very positive results [13]. Advanced control and optimization techniques can help make important decisions about complex energy systems.…”
Section: Hybrid Power Generation Applicationsmentioning
confidence: 99%
“…With the development of floating offshore wind turbines over the world, their reliability and dynamic performance requirements have gradually increased [13,14]. Although vector control theory can be used to convert a doubly-fed floating offshore wind turbine system into a linear system.…”
Section: Introductionmentioning
confidence: 99%